TEORI ADMINISTRASI HENRI FAYOL: GAGASAN, KONTRIBUSI, DAN BATASANNYA - Sukmana, Febrian Humaidi; Maryanti, Sri (UIN Mataram, 2023)
This paper aims to examine and discuss the concepts, contributions, and limitations of Henri Fayol's administrative theory in the field of management development. Many experts assert that Fayol's administrative theory has made a significant impact on the advancement of modern management. Nevertheless, this theory has also faced criticism and possesses certain constraints when applied in practice. In this study, a historical analysis methodology is employed to acquire a more profound understanding of the history, background, core ideas, implementation, and contributions of Fayol's administrative theory. Furthermore, this research critically evaluates several limitations of Fayol's administrative theory that have been previously identified in relevant literature. These limitations encompass the insufficient consideration of human factors within organizations, the influence of cultural and organizational environments, inflexibility in complex and dynamic situations, as well as an excessive focus on efficiency rather than effectiveness. Despite these limitations, Fayol's administrative theory continues to serve as a crucial foundation in the development of modern management